Relationship between leadership styles of managers and employee’s perceived job performance in a bank in Nigeria - Aishat, Olorundare Agbana (2016)
This study sets to investigate the relationship between leadership style of managers and employee’s perceived job performance in a selected bank in Nigeria, it is the aim of this study to investigates the relationship between the selected independent variables, leadership styles (transformational, transactional, laissez-faire) and perceived job performance as the dependent variables, the objectives are to determine the level of employee’s perceived job performance, determine the common leadership style that is commonly used by the bank managers, determine the relationship between leadership styles and employee perceived job performance and finally determined the predictor variable (leadership styles) on job performance.. The study used survey design to collect data from one hundred and fifty five Employee’s in zenith bank plc. Nigeria. The research utilized simple random sampling techniques; in which the populations of the study were given equal chance of being selected. The sample size was determined by G.power version 3.1. Data were collected using questionnaire that required respondent to rate their level of job performance as well as their “managers” leadership styles using five point scale likert type. The findings showed that perceived job performance is high and also the descriptive statistics revealed that the most commonly used leadership styles among the managers of Zenith Banks Plc. Nigeria is transactional leadership styles, with the highest mean of 4.18.. The result obtained from the Pearson correlational analyses revealed that there is a strong significant positive relationship between leadership styles of managers and employee perceived job performance in Zenith Bank Plc. Nigeria. The result of the multiple regression analysis at 0.01 levels of significant showed that transactional leadership style is the most predictors of job performance. It explains 44% of the variance in employee perceived job performance. The present study contributes useful information for bank managers and researchers in the field of human resource development.